2021
DOI: 10.1093/rheumatology/keab152
|View full text |Cite
|
Sign up to set email alerts
|

The clinical phenotype of systemic sclerosis patients with anti-PM/Scl antibodies: results from the EUSTAR cohort

Abstract: Objective To evaluate clinical associations of anti-PM/Scl antibodies in patients with Systemic Sclerosis (SSc) in a multicentre international cohort, with particular focus on unresolved issues, including scleroderma renal crisis (SRC), malignancies, and functional outcome of interstitial lung disease (ILD). Methods (1) Analysis of SSc patients from the EUSTAR database: 144 anti-PM/Scl+ without SSc-specific autoantibodies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 34 publications
(46 reference statements)
2
31
0
3
Order By: Relevance
“…Anti-PM/Scl (anti-PM-100 and anti-PM-75) autoantibodies are frequently reported in patients with overlap syndromes of myositis and SSc. A consistent association has been found between calcinosis and anti-PM/Scl autoantibody in SSc 3,26–29 and DM patients. 30 The association between calcinosis and scleroderma-specific autoantibodies has not been consistent.…”
Section: Epidemiologysupporting
confidence: 74%
“…Anti-PM/Scl (anti-PM-100 and anti-PM-75) autoantibodies are frequently reported in patients with overlap syndromes of myositis and SSc. A consistent association has been found between calcinosis and anti-PM/Scl autoantibody in SSc 3,26–29 and DM patients. 30 The association between calcinosis and scleroderma-specific autoantibodies has not been consistent.…”
Section: Epidemiologysupporting
confidence: 74%
“…However, it is unclear whether the malignancies in these patients are related to anti-PM/Scl syndrome because they occurred separated in time from each other, and in one patient even 6 years before the anti-PM/Scl syndrome, and one case as late as 1 year after the onset of the disease. Lazzaroni et al reported the frequency of malignancies was not significantly higher in anti-PM/Scl positive SSc patients than in anti-PM/Scl negative controls from the EULAR Scleroderma Trials and Research group (EUSTAR) database ( 19 ). More cases are needed to confirm any associations between the malignancy and the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the large cohort of 124 SSc/PM OS patients, 33.1% of patients presented anti-PM/Scl antibodies. 12 Myositis, calcinosis, mild interstitial pneumonia, and DM cutaneous signs are reported to be associated with anti-PM/Scl antibody positivity in SSc, 13 while 2-4% of patients with DM or SSc alone also present this antibody. 13 In addition, Mahler et al 14 reported that four of 100 SLE patients presented both anti-dsDNA and anti-PM/Scl antibodies.…”
Section: Discussionmentioning
confidence: 99%